Interpretive Narratives of Geoheritage: Experiences in French Geoparks - Azevedo, Úrsula Ruchkys de (Sociedade & Natureza, 2025)
This article investigates interpretive panels at geosites in three French geoparks, aiming to understand how different narrative strategies communicate aspects of geoheritage. The research adopts a qualitative approach, based on a critical analysis of 17 panels collected in the field. The theoretical framework is grounded in the heritage typology proposed by Doumit (2007), which identifies five narrative dimensions — scientific, historical, symbolic, artistic, and sensory — along with an analytical framework encompassing four interpretive approaches: educational, communicational, discursive, and integrative. The results indicate a predominance of the scientific/natural dimension in the analyzed panels, highlighting an emphasis on technical and geological aspects. However, in some cases, there is articulation with other dimensions, such as historical, symbolic, and sensory, especially when the content relates to social practices, local memories, or cultural elements. These connections enrich the interpretive experience and provide a more contextualized reading of the territory. Regarding interpretive approaches, educational and communicational orientations prevail, focusing on technical explanations and visual resources, which help make scientific content accessible to diverse audiences but tend to limit active visitor participation. In contrast, discursive and integrative approaches — which encourage visitors to co-construct meaning and foster emotional connections to places — are less frequent, indicating an underexplored potential. The discussion proposes a reflection on the role of interpretive devices as cultural mediators of territory, emphasizing their capacity to construct meaning, promote belonging, and strengthen the relationship between communities, landscapes, and local heritage. By combining knowledge, memory, and experience, such devices can contribute to broader processes of social valorization and appropriation of geoheritage. The study also engages with Brazilian experiences and reinforces the importance of interpretive strategies that integrate multiple heritage dimensions through more sensitive and participatory approaches. It advocates for cultural mediation that promotes community involvement, a sense of belonging, and actions oriented toward sustainability, thereby enhancing the social and educational impacts of geoparks.